Mesenchymal Stem Cell Senescence and Rejuvenation: Current Status and Challenges - Zhou, Xueke; Hong, Yimei; Zhang, Hao; Li, Xin (Frontiers in Cell and Developmental Biology, 2020)
Over the past decades, mesenchymal stem cell (MSC)-based therapy has been intensively investigated and shown promising results in the treatment of various diseases due to their easy isolation, multiple lineage differentiation potential and immunomodulatory effects. To date, hundreds of phase I and II clinical trials using MSCs have been completed and many are ongoing. Accumulating evidence has shown that transplanted allogeneic MSCs lose their beneficial effects due to immunorejection. Nevertheless, the function of autologous MSCs is adversely affected by age, a process termed senescence, thus limiting their therapeutic potential. Despite great advances in knowledge, the potential mechanisms underlying MSC senescence are not entirely clear. Understanding the molecular mechanisms that contribute to MSC senescence is crucial when exploring novel strategies to rejuvenate senescent MSCs. In this review, we aim to provide an overview of the biological features of senescent MSCs and the recent progress made regarding the underlying mechanisms including epigenetic changes, autophagy, mitochondrial dysfunction and telomere shortening. We also summarize the current approaches to rejuvenate senescent MSCs including gene modification and pretreatment strategies. Collectively, rejuvenation of senescent MSCs is a promising strategy to enhance the efficacy of autologous MSC-based therapy, especially in elderly patients.